(untitled) (Research, Society and Development, 2019)
With the purpose of evaluating the water balance of the dryland microculture in the municipality of Caratinga, MG, hydrological calculations are performed using the Thornthwaite - Mather method. This research is quantitative in nature and is specifically a case study. The result of the water balance has shown that the greatest months of evapotranspiration, decay, over 100 mm, took place in the months of January, August, September, October and December. Between the months of March and November occurred the largest water deficit characterizing the dry season, however the highest rainfall occurred between the months of December and February, featuring a rainy season, but humid, demonstrating that the studied area presents the well-differentiated parks and defined.